The Impact of Human Resource Quality and the Use of Accounting Information Systems on Fixed Asset Management (A Study of Employees in Kolaka Regency Government Agencies) - Piscal Permata Manga; Husin Husin; Vina Olivia Pebrianty (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The study examines the impact of human resource quality and the utilization of accounting information systems on fixed asset management within Regional Government Agencies of Kolaka Regency, Indonesia. Effective management of public assets requires competent personnel and reliable information systems to ensure accountability, transparency, and administrative accuracy. An empirical quantitative approach was employed using purposive sampling to select 120 employees directly involved in asset administration activities. Data were collected through an online questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics Version 22. Instrument testing confirmed satisfactory levels of validity and reliability, while classical assumption testing indicated that the data met the requirements for regression analysis. The findings reveal that human resource quality has a positive and significant effect on fixed asset management. The utilization of accounting information systems also demonstrates a positive and significant influence on asset management performance. Simultaneous testing confirms that both variables collectively exert a significant impact on fixed asset management effectiveness. The model explains 73.9 percent of the variance in fixed asset management outcomes, indicating substantial explanatory power. The results support the integration of Resource Based View and Technology Acceptance Model perspectives by highlighting the complementary roles of organizational competencies and digital technologies in strengthening public asset governance. The study offers practical implications for improving regional asset administration through investments in employee capability development and information system enhancement.